1970
DOI: 10.1039/j29700000855
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of aqueous solutions of p-benzoquinone: a spectrophotometric investigation

Abstract: The photolysis of aqueous solutions of p-benzoquinone is investigated spectrophotometrically over a wider range of pH, concentration, and the wavelength of irradiation than before. Experimental evidence has been obtained for the formation of benzene-I ,2,4-triol as the sole primary photochemical product at all values of pH. Quinol and 2-hydroxy-I ,4-benzoquinone are produced in equimolar quantities as secondary products both in acid and alkaline solutions, when the reaction between p-benzoquinone and benzene-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
1
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 0 publications
4
50
1
1
Order By: Relevance
“…[19] From this, a quantum yield of F(Q consumption) = 0.31 was obtained. [19] The quantum yield was found to be independent of pH in the range of pH 0.4±8. We have recently shown that HOQ is a fairly strong acid (pK a 4.2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[19] From this, a quantum yield of F(Q consumption) = 0.31 was obtained. [19] The quantum yield was found to be independent of pH in the range of pH 0.4±8. We have recently shown that HOQ is a fairly strong acid (pK a 4.2).…”
Section: Resultsmentioning
confidence: 99%
“…We had used the electrochemical oxida- 442 FULL PAPER tion of 1,2,4-trihydroxybenzene (Ph(OH) 3 ) to generate HOQ, [71] but its oxidation by Q [19] (reaction 8; for the kinetics of this reaction see below) is an alternative and more convenient procedure that was now used for calibration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The concentrations of the stock solutions in our experiments were typically 1×10 -3 mol dm -3 . 1,4-Benzoquinones are photosensitive compounds in solution, 7,8,[31][32][33][34][35][36][37] therefore fresh solutions were prepared for all experiments in brown glass volumetric flask.…”
Section: Methodsmentioning
confidence: 99%
“…Esse provavelmente é o principal motivo para a não detecção, ou detecção de valores extremamente baixos, de p-benzoquinona em estudos já publicados envolvendo hidroxilação de fenol monitorados por cromatografia gasosa. Além disso, a p-benzoquinona, em meio aquoso e sob luz, é capaz de clivar as moléculas de água, formando o radical hidroxila [99], [100], [101] . …”
Section: Figura 37 -Estruturas Do Fenol E Dos Compostos Formados Na Runclassified